Defined serum‐free three‐dimensional culture of umbilical cord‐derived mesenchymal stem cells yields exosomes that promote fibroblast proliferation and migration in vitro. Issue 1 (25th December 2020) - Faruqu, Farid N.; Liam‐Or, Revadee; Zhou, Shuai; Nip, Rebecca; Al‐Jamal, Khuloud T.
Abstract: Stem cell‐derived exosomes are emerging as novel and clinically relevant cell‐free therapeutics for regenerative therapy. This work focused on investigating the stimulation of fibroblasts by exosomes derived from umbilical cord‐derived mesenchymal stem cells (ucMSC) in a defined serum‐free three‐dimensional (3D) culture. 3D culture of ucMSC was carried out in medium supplemented with KnockOut serum replacement (KO‐medium) using the Aggrewell system. ucMSC in KO‐medium formed spheroids with maintained size and integrity throughout culture. This enabled the isolation of vesicles from ucMSC spheroids in KO‐medium with sizes that fall within the exosomal size range and were positive for the expression of canonical exosomal markers CD63, CD9, CD81, Alix, and TSG101. The ucMSC‐derived exosomes (ExoucMSC ) were shown to significantly increase the migration and proliferation of murine fibroblasts in vitro. To conclude, 3D culture of ucMSC in defined serum‐free KO‐medium formed viable spheroids which enabled the isolation of ExoucMSC with the potential of accelerating wound healing.